Validity and Reliability of Malaysian Sports Culture Index Instrument (MSCI’2020) (International Journal of Physiotherapy, 2022)
Background: Malaysian Sports Culture Index (MSCI) is an evaluation system to measure the sports culture index among the Malaysian population. This study aims to validate and measure the reliability of the Malaysian Sports Culture Index questionnaire. The evaluation process needs a standard instrument to generalize the findings accurately for the targeted Malaysian population.Methods: The Malaysian Sports Culture Index (MSCI’2020), an instrument built with five domains and eight indicators in a questionnaire by the Institute for Youth Research Malaysia (IYRES), Malaysia’s Ministry of Youth and Sport. The five domains in this questionnaire are Participation, Passion for sports, Volunteerism, Expenditure, and Facility. The survey was conducted among 150 respondents selected randomly to get the reliability using the Cronbach Alpha test. This pilot study also selected five experts to validate the content by domains and indicators.Results: The findings proved that this MSCI’2020 instrument has very high content validity, r=.93. The reliability analysis based on domain and indicator showed Domain Passion for sports r=.91; meanwhile, the two indicators also have high reliability. Indicator Attachment r=.84 and Indicator Dedication r=.90. In the second Domain, volunteerism showed r=.91; meanwhile, indicator sponsorship r=.88 and indicator volunteer service r=.91. The alpha value for Domain Expenditure is r=.86, and the domain facility also has a high validity of r=.98.Conclusion: This pilot study proved that the Malaysian Sports Culture Index (MSCI’2020) questionnaire is valid and reliable for measuring the Malaysian population’s sports culture index. The data collected for this research will give us meaningful feedback on the trend of participation in sports activities, physical exercise, and recreation activities as a culture among Malaysians. This study also indicates that this instrument can be adapted or used as a guideline for further studies.